Teaching styles and parental bonding as correlates of academic boredom among undergraduates in Oyo State (2024)
This study investigates the relationship between teaching techniques, parental bonding, and the factors that lead to academic boredom among undergraduates in Oyo State. The study employed a non-experimental design of correlational research type. A total of 250 undergraduates (107 males and 143 females) were randomly picked from three institutions in Oyo State. The age range of the individuals was between 16 and 26 years, with an average age of 16.83. Three assessments with demonstrated validity and reliability were employed to assess teaching styles, parental bonding, and academic boredom. The data was analyzed using Pearson's Product Moment Correlation and multiple regression at a significance threshold of 0.05. The findings indicated a strong correlation between teaching styles and academic boredom (r=0.21; p<0.05), as well as parental bonding (r=0.33; p<0.05). The combination of teaching styles and parental bonding accounted for 20.8% of the Variation in predicting academic boredom. Furthermore, the study found that teaching styles (ß= -0.39, t=-3.66; p<0.05) and parental bonding (ß=0.366, t=4.91; p<0.05) significantly predicted academic boredom. This could prompt the undergraduates to request the necessary educational resources for their studies. Additionally, it could foster a greater enthusiasm for academic tasks, thereby eliminating feelings of boredom. Therefore, itis recommended that parents should prioritize establishing a deep emotional connection with their children and wards.